Amelioration of the Behavioral Phenotype in Genetically Ataxic Mice through Bilateral Intracerebellar Grafting of Fetal Purkinje Cells - Lazaros C. Triarhou; Zei Zhang; Wei-Hua Le (Cell Transplantation, 1996)
We have previously applied neural grafting to “Purkinje cell degeneration” mutant mice (gene symbol pcd, mouse chromosome 13), a model of recessively inherited cerebello-olivary atrophy, to create appropriate interactions between wild-type and mutant cells in elucidating gene effects on the involved neuron populations and to address issues of the structural integration of donor Purkinje cells into the disrupted cerebellar loop. Behaviorally, pcd homozygotes manifest ataxic signs beginning at 3-4 wk of age. The functional effects of cerebellar transplants on motor performance have long remained an open question. The aim of the present study was to determine the recovery of motor responses in pcd mutants in a battery of behavioral tasks after bilateral transplantation of cerebellar cell suspensions (prepared from wild-type mice) into the parenchyma of the deep cerebellar nuclei of the hosts, according to a protocol that emphasizes the reconstruction of the missing inhibitory cortico-nuclear projection. With this approach, the denervated deep nuclei of the host receive a new Purkinje axonal innervation; further, most transplanted Purkinje cells end up occupying cortical localities anyway and display a correct dendritic tree orientation toward the pia. Motor coordination and fatigue resistance were assessed in a rotarod treadmill apparatus, a behavioral paradigm useful in studying various brain abiotrophies and treatments, including developmental perturbations of the cerebellar cytoarchitecture. Locomotor activity was quantified by the number of squares mice crossed as they moved about in an open-field matrix. Grafted pcd mice performed significantly better than sham-operated mutants in both of these tasks. Moreover, graft-recipient mice were able to sustain their abdomen above the floor on their limbs during movement, contrasting to the typical lowered, widened stance of sham-operated pcd mutants. These findings clearly demonstrate that bilateral transplants of fetal Purkinje cells have functional effects on motor performance in the pcd model of hereditary cerebellar ataxia.